Minimal infectious dose and dynamics of Babesia microti parasitemia in a murine model. Issue 12 (28th September 2018) - Bakkour, Sonia; Chafets, Daniel M.; Wen, Li; Muench, Marcus O.; Telford, Sam R.; Erwin, James L.; Levin, Andrew E.; Self, Deanna; Brès, Vanessa; Linnen, Jeffrey M.; Lee, Tzong‐Hae; Busch, Michael P.
Abstract : BACKGROUND: Babesia microti is a parasite that infects red blood cells (RBCs) in mammals. It is transmitted to humans by tick bites, transfusion, organ transplantation, and congenital acquisition. Although the Babesia natural history and seroprevalence in donors have been well described, gaps in knowledge relevant to transfusion remain. STUDY DESIGN AND METHODS: Mice were infected with dilutions of parasitized blood to address the minimal infectious dose and the kinetics of parasitemia by quantitative polymerase chain reaction (qPCR) and of antibodies by enzyme immunoassay. RESULTS: In immunocompetent DBA/2 mice infected with 100 parasitized RBCs (pRBCs) and in immunodeficient NSG mice infected with 63 pRBCs, parasitemia was detectable in five of five mice each. Peak parasitemia up to 2 × 10 7 pRBCs/mL at 2 to 3 weeks or 5 × 10 8 pRBCs/mL at 6 weeks was observed for DBA/2 and NSG mice, respectively. Protracted fluctuating parasitemia was observed for 8 months in DBA/2 mice, whereas NSG mice exhibited a high‐plateau parasitemia. Antibody titers continued to increase until 6 to 18 weeks in DBA/2 mice and remained high through 6 months. This study also investigated the analytical performance of Babesia assays that detect parasite DNA or RNA using a blinded panel. A Babesia assay targeting parasite RNA was approximately 10‐fold more sensitive compared to qPCR targeting DNA. CONCLUSION: The mice in this study were highly susceptible to Babesia infection using as few as 1 to 2 log pRBCs and maintained chronic parasitemia. If the infectious dose in human transfusion recipients is comparably low, a highly sensitive assay targeting parasite RNA may safeguard the blood supply, particularly before antibody detection.